THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK RETURNS ( EMPIRICAL STUDY ON FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2016-2020) - Sari, Fitri Arinta; Faisol, Ahmad; Lazuardi, Yanuar; Anshori, Zakaria; Kurniyawati, Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research aims to determine the effect of financial performance on stock returns . The dependent variable used is Stock Return while the independent variables are Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Assets (ROA) . The population in this research is Food and Beverage companies listed on the Indonesia Stock Exchange (BEI) in 2016-2020. The sampling technique uses a purposive sampling method . Of the 30 companies listed on the Indonesia Stock Exchange (BEI), only 17 companies were used as samples for this research. The data analysis technique uses multiple linear regression analysis with SPSS20. Before carrying out multiple regression analysis, the classical assumptions are first tested. Based on the results of hypothesis testing, it shows that there is one variable, namely Debt to Equity Ratio (DER) , which has a significant positive effect on stock returns , while the Current Ratio (CR) and Return On Assets (ROA) have no significant effect on Stock Returns .